Cognitive, Social, and Teaching Presences among Postgraduate Students on the Mobile Instant Messaging Platform - Siti Norzaimalina, Abd Majid; Abdul Rahim, Salam (AWEJ.org, 2023)
This study examines the portrayal of cognitive, social, and teaching presence among postgraduate students using mobile instant messaging in a fully online learning environment. Understanding the portrayal of these presences can help researchers to gain insights into the specific dynamics of these presences and develop strategies to optimize the learning experience among postgraduate students. However, a lack of evidence on how cognitive, social, and teaching presence is portrayed in this platform makes it difficult to identify possible gaps where postgraduates may need more assistance. This study conducted a qualitative content analysis of 2074 messages from four groups on WhatsApp’s mobile instant messaging application. From the research, 68% of the messages demonstrated social presence, 25% teaching presence, and 7% indicated cognitive presence. The cognitive presence on WhatsApp was the least demonstrated, as students preferred rich mediums like video conferencing to engage in discussions that require higher-order thinking skills. Future research can consider analyzing how students show presences using multiple mediums and explore how cognitive, social, and teaching presences are dynamically interplayed in different mediums using a qualitative approach.